Apical versus Non‐Apical Lead: Is ICD Lead Position Important for Successful Defibrillation?. (5th April 2016) - AMIT, GUY; WANG, JIA; CONNOLLY, STUART J.; GLIKSON, MICHAEL; HOHNLOSER, STEPHAN; WRIGHT, DAVID J.; BRACHMANN, JOHANNES; DEFAYE, PASCAL; NEUZNER, JOERG; MABO, PHILIPPE; VANERVEN, LISELOT; VINOLAS, XAVIER; et al.
ICD Lead Position and Outcome: Introduction: We aim to compare the acute and long‐term success of defibrillation between non‐apical and apical ICD lead position. Methods and Results: The position of the ventricular lead was recorded by the implanting physician for 2, 475 of 2, 500 subjects in the Shockless IMPLant Evaluation (SIMPLE) trial, and subjects were grouped accordingly as non‐apical or apical. The success of intra‐operative defibrillation testing and of subsequent clinical shocks were compared. Propensity scoring was used to adjust for the impact of differences in baseline variables between these groups. There were 541 leads that were implanted at a non‐apical position (21.9%). Patients implanted with a non‐apical lead had a higher rate of secondary prevention indication. Non‐apical location resulted in a lower mean R‐wave amplitude (14.0 vs. 15.2, P < 0.001), lower mean pacing impedance (662 ohm vs. 728 ohm, P < 0.001), and higher mean pacing threshold (0.70 V vs. 0.66 V, P = 0.01). Single‐coil leads and cardiac resynchronization devices were used more often in non‐apical implants. The success of intra‐operative defibrillation was similar between propensity score matched groups (89%). Over a mean follow‐up of 3 years, there were no significant differences in the yearly rates of appropriate shock (5.5% vs. 5.4%, P = 0.98), failed appropriate first shock (0.9% vs. 1.0%, P = 0.66), or the composite of failed shock or arrhythmic death (2.8% vs. 2.3% P = 0.35) according to lead location. Conclusion: We did not detect any reduction in the ICD efficacy at the time of implant or during follow‐up in patients receiving a non‐apical RV lead.